Establishment of Early Multi-Indicator Prediction Models of Moderately Severe Acute Pancreatitis and Severe Acute Pancreatitis. (4th April 2022) - He, Shan-Shan; Li, Dan; He, Qi-Yong; Chen, Xiao-Ping; Lin, Yong-Xu; Yu, Yun-Wen; Chen, Feng-Lin; Ding, Jian
Abstract : Background . It is critical to accurately identify patients with severe acute pancreatitis (SAP) and moderately SAP (MSAP) in a timely manner. The study was done to establish two early multi-indicator prediction models of MSAP and SAP. Methods . Clinical data of 469 patients with acute pancreatitis (AP) between 2015 and 2020, at the First Affiliated Hospital of Fujian Medical University, and between 2012 and 2020, at the Affiliated Union Hospital of Fujian Medical University, were retrospectively analyzed. The unweighted predictive score (unwScore) and weighted predictive score (wScore) for MSAP and SAP were derived using logistic regression analysis and were compared with four existing systems using receiver operating characteristic curves. Results . Seven prognostic indicators were selected for incorporation into models, including white blood cell count, lactate dehydrogenase, C-reactive protein, triglyceride, D-dimer, serum potassium, and serum calcium. The cut-offs of the unwScore and wScore for predicting severity were set as 3 points and 0.513 points, respectively. The unwScore (AUC = 0.854 ) and wScore (AUC = 0.837 ) were superior to the acute physiology and chronic health evaluation II score (AUC = 0.526 ), the bedside index for severity in AP score (AUC = 0.766 ), and the Ranson score (AUC = 0.693 ) in predicting MSAP and SAP, which were equivalent to the modified computed tomography severity index score (AUC = 0.823 ). Conclusions . The unwScore and wScore have good predictive value for MSAP and SAP, which could provide a valuable clinical reference for management and treatment.